2017
DOI: 10.3390/ijms19010082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neurobehavioral Features of Three Novel Kabuki Syndrome Patients with Mosaic KMT2D Mutations and a Review of Literature

Abstract: Kabuki syndrome (KS) is a rare disorder characterized by multiple congenital anomalies and variable intellectual disability caused by mutations in KMT2D/MLL2 and KDM6A/UTX, two interacting chromatin modifier responsible respectively for 56–75% and 5–8% of the cases. To date, three KS patients with mosaic KMT2D deletions in blood lymphocytes have been described. We report on three additional subjects displaying KMT2D gene mosaics including one in which a single nucleotide change results in a new frameshift muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…We identified a nonsense variant of KMT2D with a mosaicism level of 37.0% in one male patient (KMS-025). Although he showed the typical facial features of KS and multisystem abnormalities, his features and intellectual disability were milder than those reported previously in mosaic cases (Banka et al, 2013;Lepri et al, 2017). He was enrolled in a special education class in preschool, but went on to attend a normal class in elementary school.…”
Section: Discussionmentioning
confidence: 69%
“…We identified a nonsense variant of KMT2D with a mosaicism level of 37.0% in one male patient (KMS-025). Although he showed the typical facial features of KS and multisystem abnormalities, his features and intellectual disability were milder than those reported previously in mosaic cases (Banka et al, 2013;Lepri et al, 2017). He was enrolled in a special education class in preschool, but went on to attend a normal class in elementary school.…”
Section: Discussionmentioning
confidence: 69%
“…The authors applied our proposed diagnostic criteria to three individuals with mosaic KS reported in the literature 37. Each reported patient had a mosaic heterozygous pathogenic variant in KMT2D and was reported to have mild clinical features of KS.…”
Section: Discussionmentioning
confidence: 99%
“…Mhanni et al (1999) showed that all individuals with this syndrome presented similar physiognomy, which simplified the recognition of the syndrome in childhood. Three other case reports from different authors have shown 100% of physiognomy changes that are typical of the syndrome (MCGAUGHRAN et al, 2001;LEPRI et al, 2017;XIN et al, 2018), suggesting that such observations are of considerable importance and make it possible to diagnose the syndrome based on phenotype.…”
Section: Discussionmentioning
confidence: 95%